2013
DOI: 10.3133/sir20135106
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic and water-quality data collection for the investigation of Great Lakes tributaries for Asian carp spawning and egg-transport suitability

Abstract: For more information on the USGS-the Federal source for science about the Earth, its natural and living resources, natural hazards, and the environment, visit http://www.usgs.gov or call 1-888-ASK-USGS.For an overview of USGS information products, including maps, imagery, and publications, visit http://www.usgs.gov/pubprodTo order this and other USGS information products, visit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 4 publications
3
64
0
Order By: Relevance
“…The reported peak transport time from the Berrien Springs Dam to the settling zone where the Saint Joseph River transitions to backwater conditions from Lake Michigan (36.8 km downstream from Berrien Springs Dam) was approximately 16 h with leading and trailing edge transport times of 15 and 20 h, respectively . Comparing the egg travel times with the estimated hatching time for silver carp at typical summertime water temperatures (18.7 h at 26.5°C), Murphy and Jackson (2013) concluded that only a small fraction of the eggs might hatch before reaching the lake. However, the authors suggested that lower flow rates and higher water temperatures may increase the fraction of the eggs that could potentially hatch before reaching Lake Michigan .…”
Section: Methodsmentioning
confidence: 98%
See 3 more Smart Citations
“…The reported peak transport time from the Berrien Springs Dam to the settling zone where the Saint Joseph River transitions to backwater conditions from Lake Michigan (36.8 km downstream from Berrien Springs Dam) was approximately 16 h with leading and trailing edge transport times of 15 and 20 h, respectively . Comparing the egg travel times with the estimated hatching time for silver carp at typical summertime water temperatures (18.7 h at 26.5°C), Murphy and Jackson (2013) concluded that only a small fraction of the eggs might hatch before reaching the lake. However, the authors suggested that lower flow rates and higher water temperatures may increase the fraction of the eggs that could potentially hatch before reaching Lake Michigan .…”
Section: Methodsmentioning
confidence: 98%
“…In the new version of FluEgg, the approximate hatching time is calculated based on the temperature averaged over all the cells. FluEgg uses an empirical function derived from the compilation completed by Murphy and Jackson (2013) on hatching times as a function of temperature. For a given species the hatching time is calculated based on the temperature averaged over all the cells as follows: …”
Section: Egg Hatching Timementioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, lake connected rivers have significant benefits on the carp life cycle. The U.S. Geological Survey study identified that the Maumee and other rivers flowing into Lake Erie have the right conditions to serve as spawning sites for Asian carps (Murphy and Jackson, 2013).…”
Section: Habitat Suitability In the Fluvial And Lacustrine Regionsmentioning
confidence: 99%